Linguistic Landscape Of Coffee Shop Names In Yogyakarta: An Antropolinguistics Study - Amrina, Lia Amalia; Christian, Adhitya Rechandy (Angstrom Centre of Education, 2025)
The linguistic landscape of coffee shop signboards in Yogyakarta, Indonesia reflects the city's multicultural and multilingual character. This study examines the forms, meanings, and origins of coffee shop names in Yogyakarta by presenting photographic examples from four districts and cities. Coffee shops can be classified as monolingual, multilingual, or bilingual. Various languages are employed, including Indonesian, Javanese, and English. The meanings of names can be linked to regional origins, local landmarks, wordplay, and cultural references. The origins of the names are often tied to the history and culture of Yogyakarta, such as local legends, arts, and traditions. The prevalence of Indonesian and English alongside local languages suggests a multilingual environment influenced by cultural, commercial, and regulatory factors. The strategic placement of linguistic elements in signage, menu descriptions, and promotional materials attracts and caters to a sophisticated customer base. The linguistic choices made by coffee shop owners and managers can be viewed as deliberate efforts to cultivate a particular atmosphere and ambiance. This study provides insights into the diverse naming practices of coffee shops in Yogyakarta, offering a reference for further research on the city's coffee culture and its linguistic landscape.